Agricultura familiar camponesa no Pantanal brasileiro : a produção agropecuária e as estratégias de comercialização em assentamentos rurais no município de Cáceres - MT - Amaral, Rodrigo Klinsmann Silva do (2022)
This dissertation aims to analyze the production and destination carried out by the agrarian reform settlements in the municipality of Cáceres, belonging to the Pantanal of Mato Grosso, and the importance of territory, as a category of analysis regarding the reproduction of settled peasant family farmers. For this, we used data collected and tabulated by the Project of Diagnosis for Environmental Regularization of Agrarian Reform Settlements - RADIS/UFMT, which by means of interviews conducted in the years 2019 and 2020, obtained 3,207 interviews in rural settlements located in five municipalities of Mato Grosso, of these, the one with the highest number of interviews conducted was chosen, Cáceres, with 1,331 interviews, distributed in 15 settlements. Thus, a new tabulation was elaborated, in order to extract only the relevant data for the research in question, which could be divided into two categories "Labor and income relations" and "Production and commercialization". The results show that the struggle for land, intensified in the region in the 1990's, was essential for the territorialization/reterritorialization of the peasants currently settled. However, this has not yet been able to make significant changes in the Pantanal land structure, historically concentrated, due to different factors, besides the territorialization of capital, which in Brazil is characterized by monoculture in large extensions of land. In this biome, it was verified the presence of large properties, existing since the period of Sesmarias, which are justified by those who own them, by the physical characteristics of the Pantanal, marked by extensive floodable areas. As for production, it was found that most of the producers reproduce beef cattle raising, an activity that has historically predominated in the entire Pantanal, and dairy cattle raising also deserves to be highlighted, although practiced by a smaller portion of the settlers; both activities act as an important source of provisioning and income for the settlers. Agriculture for commercialization, on the other hand, is little practiced. It is important to emphasize the relevance of productive backyards, used mainly for family consumption, and which should be valued for the role they play from a socioeconomic point of view. It is observed, therefore, that the rural settlements in the municipality of Cáceres have an important responsibility, especially for the settlers, since it allows their social reproduction. However, it is necessary to intensify the performance of the public power in two fronts, one aimed at the development and greater integration field-city of the already existing settlements, and the other to strengthen the agrarian reform, in order to deconcentrate the Pantanal landholding structure. These are the paths that are understood to be primordial for the democratization of access to land and the construction of a more just society.